Deposition and provenance of the Early Pleistocene Siliceous Member in Westbury Cave, Somerset, England. Issue 2 (April 2019) - Adams, Neil F.; Candy, Ian; Schreve, Danielle C.; Barendregt, René W.
Abstract: The Early Pleistocene is an important interval in the Quaternary period as a time not only of climatic and environmental change, but also of key events in human evolution. However, knowledge of this period in northwest Europe is hampered by the limited extent of deposits of this age. Westbury Cave in the Mendip Hills of Somerset preserves an understudied example of fossil-bearing Early Pleistocene sediments, with rare potential to inform our understanding of British Early Pleistocene stratigraphy and landscape evolution outside the East Anglian Crag Basin. This study identifies the processes responsible for deposition of the Early Pleistocene Siliceous Member in Westbury Cave, thereby aiding taphonomic and palaeoenvironmental interpretations of associated fossil assemblages. New excavations revealed over ten metres of Siliceous Member stratigraphy, dominated by fine-grained silts/clays with interbedded sands and gravels, interpreted as being deposited within a subterranean lake or flooded conduit with fluvial input. All sediments sampled were reversely magnetised and are assigned to the Matuyama Reversed Chron. Lithological analysis of gravel clasts revealed variable components of durable non-local and non-durable local clasts. Gravels containing the latter are interpreted as distal talus slope deposits, and those lacking non-durable lithologies as stream or flood deposits. However, it remains unclear from available data whether apparently non-local clasts were sourced from long distance or stem from a more local, now denuded catchment. Siliceous Member bio- and magnetostratigraphy suggest that deposition occurred late in the Early Pleistocene, a period apparently otherwise unrepresented in the UK.